2005
DOI: 10.1007/s11005-005-0015-9
|View full text |Cite
|
Sign up to set email alerts
|

Dual Canonical Bases for the Quantum Special Linear Group and Invariant Subalgebras

Abstract: Abstract. A string basis is constructed for each subalgebra of invariants of the function algebra on the quantum special linear group. By analyzing the string basis for a particular subalgebra of invariants, we obtain a "canonical basis" for every finite dimensional irreducible U q (sl(n))-module. It is also shown that the algebra of functions on any quantum homogeneous space is generated by quantum minors.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…A brief review of early works on the theory and applications of quantum supergroups can be found in [63]. Partially successful constructions of crystal and canonical bases for quantum supergroups were given in [1,12,37,53,55,54,72,73].…”
Section: Introductionmentioning
confidence: 99%
“…A brief review of early works on the theory and applications of quantum supergroups can be found in [63]. Partially successful constructions of crystal and canonical bases for quantum supergroups were given in [1,12,37,53,55,54,72,73].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a similar argument as that in [14] shows that the subalgebra O q (G/K) is spanned by the elements of the basis B * m|n which are invariant under L Uq(k) . Let U q (k) be the subalgebra U q (n + ).…”
Section: Zhang Hechunmentioning
confidence: 58%
“…The action of the Kashiwara operators for those even Chevalley generators can be described in the same way as in [14]. A similar argument as that in [14] also shows that for any matrix A ∈ M and i = 1, 2, .…”
Section: Zhang Hechunmentioning
confidence: 63%
See 1 more Smart Citation
“…Now, the same argument as in [21] shows that the subalgebra of invariants is spanned by a part of the dual canonical basis. 2…”
mentioning
confidence: 80%